Seeing in the Dark : A Machine-Learning Approach to Nowcasting in Lebanon - Tiffin, Andrew (Washington, D.C. : International Monetary Fund, 2016)
Macroeconomic analysis in Lebanon presents a distinct challenge. For example, long delays in the publication of GDP data mean that our analysis often relies on proxy variables, and resembles an extended version of the 'nowcasting' challenge familiar to many central banks. Addressing this problem-and mindful of the pitfalls of extracting information from a large number of correlated proxies-we explore some recent techniques from the machine learning literature. We focus on two popular techniques (Elastic Net regression and Random Forests) and provide an estimation procedure that is intuitively familiar and well suited to the challenging features of Lebanon's data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: GDP; Macroeconomic Forecasts; Nowcasting; Random Forests; WP; Lebanon